Casting And Cooling/Crushing Of Silicon Metal And Silicon Alloy At Bécancour Silicon Inc. - R. Boisvert; D. Leblanc; D. Ksinsik (The Southern African Institute of Mining and Metallurgy, 2004)
Casting, cooling and crushing/sieving of ferroalloys has followed a well-established pattern in the whole ferroalloys industry for many years. Usually liquid metal or alloys are cast into flat open moulds of various shapes and forms, and after solidification the product is removed from such mould to further cool down to a temperature where subsequent handling steps are feasible. Common to all mechanical product fractioning is the generation of dust and fine size material with lower product value. For almost 10 years, Bécancour Silicon has investigated alternative roads to improve technology and/or reduce or solve problems related to those disadvantages. Since 1995 Bécancour Silicon operates a special silicon granulation plant targeted to product for the chemical treatment/conversion of silicon for silicones production. Prior to the development of the granulation process, various systems had been evaluated, among others the vibrating casting bed, now in operation elsewhere but judged inappropriate because of the tapping volumes to be handled at Bécancour Silicon and other disadvantages. After evaluation of all aspects of heat transfer, radiation, and conductivity in relation to transfer media and within the product, a novel system was designed and built.